2016
DOI: 10.4149/gpb_2015046
|View full text |Cite
|
Sign up to set email alerts
|

Role of acid sphingomyelinase in the age-dependent dysregulation of sphingolipids turnover in the tissues of rats

Abstract: Old age-associated pathologies usually coincide with altered sphingolipid metabolism. In the present article, the role of acid sphingomyelinase (ASMase) in the age-dependent changes of sphingomyelin (SM) and ceramide contents in the tissues has been investigated by means of ASMase inhibitors, imipramine and zoledronic acid. It has been determined that ceramide content and ceramide/SM ratio increased, while SM level decreased in the heart, liver, blood serum and skeletal muscles of 24-month old rats in contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Intriguingly, a recent study noted that ASM activity increased significantly in plasma from older versus younger individuals 45 . Similarly, old rodents also showed high levels of ASM activity in the plasma compared to that of younger animals 45,46 . This aging-associated increase in plasma ASM is probably related to ASM secreted from ECs in the brain or peripheral blood vessels.…”
Section: Asm In Aged Plasmamentioning
confidence: 89%
See 1 more Smart Citation
“…Intriguingly, a recent study noted that ASM activity increased significantly in plasma from older versus younger individuals 45 . Similarly, old rodents also showed high levels of ASM activity in the plasma compared to that of younger animals 45,46 . This aging-associated increase in plasma ASM is probably related to ASM secreted from ECs in the brain or peripheral blood vessels.…”
Section: Asm In Aged Plasmamentioning
confidence: 89%
“…ASM can also be preferentially transported to the outer leaflet of the cell membrane and secreted into the extracellular space during cellular stress and disease 29,30 . Previous studies have reported that the expression and activity of ASM change with age [45][46][47] . Thus, in this section, we review the critical roles of ASM in association with aging-related dysfunctions in physiological processes.…”
Section: Role Of Asm In Agingmentioning
confidence: 99%
“…Serum levels of selected sphingomyelins correlate with progression from MCI to AD [ 82 ] ↓ S1P/sphingosine ratio in human aging hippocampus (only in females) [ 83 ] ↓ S1P levels in human AD brain hippocampus and inferior temporal cortex; hippocampal changes correlate with Braak stage of neuropathology [ 79 ] ↑ human hippocampal ceramide [ 83 ]. ↑ ceramide/sphingomyelin ratio in the rat serum, liver, heart, and skeletal muscle [ 84 ]. ↑ various human ceramide species [ 85 ].…”
Section: Bioactive Sphingolipids In Agingmentioning
confidence: 99%
“…↑ various human ceramide species [ 85 ]. ↑ ceramide/sphingomyelin ratio in the rat serum, liver, heart, and skeletal muscle [ 84 ]. Contradictory changes of various ceramides in centenarians [ 80 ] ↑ human brain ceramide levels—including the earliest clinically recognizable AD stage (MCI) [ 77 , 86 88 ] ↑ human hippocampal sphingomyelin level [ 83 ].…”
Section: Bioactive Sphingolipids In Agingmentioning
confidence: 99%
“…Thus, this modification ASMase expression could play in important role in changes of SL turnover observed with age (see above). Using various ASMase inhibitors, Babenko et al ( 73 ) demonstrated that downregulation of ASMase reduced skeletal muscle ceramide content and ceramide/SM ratio and increased SM of old rats to the levels close to those observed in young animals. Unfortunately, S1P content had not been assessed in these conditions.…”
Section: Sphingolipids and The Regulation Of Muscle Biologymentioning
confidence: 96%